Faktor Penyebab Mahasiswa Kesehatan Masyarakat Mengerjakan Tugas Menjelang Deadline - Anggi Maharani Syah Putri; Irham Irham; Sahir Sahir (Jurnal Kesehatan Nusantara (JKN), 2025)
Academic procrastination has become a common phenomenon among students, especially as deadlines approach.This study aims to identify the factors that cause students of the Public Health Study Program at Muhammadiyah University Parepare, to tend to complete their assignments close to the deadline.The research uses a descriptive quantitative approach with purposive sampling technique, involving 12 respondents who voluntarily filled out the questionnaire.Data were collected through questionnaires in the form of a Likert scale and analyzed using descriptive statistics.The research results indicate that internal factors such as increased motivation as deadlines approach, the tendency to procrastinate due to laziness, and difficulty starting tasks are the main causes.External factors that support this behavior include a heavy workload at the same time and busyness outside of classes.Most students feel more focused and productive when the deadline approaches.In conclusion, the combination of internal and external factors plays a significant role in students' tendency to procrastinate on assignments until the deadline approaches